2021
DOI: 10.1101/2021.12.17.473164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synuclein alpha accumulation mediates podocyte injury in Fabry nephropathy

Abstract: Current therapies for Fabry disease are based on reversing intra-cellular accumulation of globotriaosylceramide (Gb3) by enzyme replacement therapy (ERT) or chaperone-mediated stabilization of the defective enzyme, thereby alleviating lysosome dysfunction. However, their effect in the reversal of end-organ damage, like kidney injury and chronic kidney disease remains unclear. First, ultrastructural analysis of serial human kidney biopsies showed that long-term use of ERT reduced Gb3 accumulation in podocytes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Although accumulation of globotriaosylceramide in lysosomes has been considered the major pathologic factor in Fabry disease, 85 Fabian Braun illustrated a globotriaosylceramide-independent accumulation of pathogenic synuclein α in Fabry podocytes. 86 Finally, Fabiola Terzi investigated the effect of aging on glomerular signaling and showed that aging-associated signaling from PAI-1–positive senescent endothelial cells contributes to podocyte loss and glomerular scarring. 87 Both PAI-1 inhibition and senolysis rescued podocyte numbers in aging mice, and PAI-1 expression was found as a predictor of kidney transplant survival.…”
Section: Cell-cell and Cell-matrix Signalingmentioning
confidence: 99%
“…Although accumulation of globotriaosylceramide in lysosomes has been considered the major pathologic factor in Fabry disease, 85 Fabian Braun illustrated a globotriaosylceramide-independent accumulation of pathogenic synuclein α in Fabry podocytes. 86 Finally, Fabiola Terzi investigated the effect of aging on glomerular signaling and showed that aging-associated signaling from PAI-1–positive senescent endothelial cells contributes to podocyte loss and glomerular scarring. 87 Both PAI-1 inhibition and senolysis rescued podocyte numbers in aging mice, and PAI-1 expression was found as a predictor of kidney transplant survival.…”
Section: Cell-cell and Cell-matrix Signalingmentioning
confidence: 99%